Postoperative hyperlactatemia and serum lactate level trends among heart transplant recipients - Kędziora, Anna; Wierzbicki, Karol; Piątek, Jacek; Hymczak, Hubert; Górkiewicz-Kot, Izabela; Milaniak, Irena; Tomsia, Paulina; Sobczyk, Dorota; Drwila, Rafal; Kapelak, Boguslaw (PeerJ, 2020)
Background Advanced heart failure (HF), that affects 10% of the HF population, is associated with high mortality rate, meeting 50% at 1-year from diagnosis. For these individuals, heart transplantation (HTX) remains the ultimate and the gold-standard treatment option. Serum lactate level measurements has been proven useful for determining the outcome following other cardiac surgeries and among critically ill patients. Increased serum lactate levels are expected following HTX; however, no detailed analysis has been yet performed in this population. The research aims to estimate the prevalence of hyperlactatemia and describe early postoperative serum lactate level trends among heart transplant recipients. Materials and Methods Forty-six consecutive patients, who underwent HTX between 2010 and 2015, were enrolled into the retrospective analysis. Serum lactate level measurements within first 48 hours post-HTX were obtained every 6 hours from routinely conducted arterial blood gas analyses. The threshold for hyperlactatemia was considered at >1.6 mmol/L, according to upper limit of normal, based on internal laboratory standardization. The highest observed measurement within the observation, regardless of the time point of observation was determined for each patient individually and was appointed as Peak Value. Results Consecutively measured serum lactate levels differed in time (p = 0.000), with the initial increase and subsequent decrease of the values (4.3 vs. 1.9 mmol/l; p = 0.000). The increase from the baseline level to the Peak Value was statistically significant (4.3 vs. 7.0 mmol/l; p = 0.000). Various serum lactate level trends were identified, with one or more hyperlactatemia episodes. Eventually, 50% of the individuals had normal serum lactate levels at the end of the study, and hyperlactatemia was observed in the other half. Conclusions Throughout the observation, all of the patients experienced at least one episode of hyperlactatemia, with the median Peak Value of 7.0 (4.5–8.4) mmol/L. Various serum lactate level trends can be identified in post-HTX patients. Further research is required to determine the clinical usefulness of newly reported serum lactate level trends among heart transplant recipients.
Keywords: Heart transplantation; Postoperative management; Intensive Care Unit; Serum lactate level; Lactic acidosis; HTX; Early recipient care; Transplantology